Kommunikationsstrategi för Renbruksplan - Vestman, Hanna; Wennström, Ragna (2013)
The reindeer planning system (Renbruksplanen, RBP) is a communication and planning tool designed for Sami groups. A key purpose of this is that it will act as a tool in consultation with other market players, including forestry. Sami groups have asked for a model of how this can be used in a flexible manner. With the Swedish Forest Agency as a project manager, a communication model for how to use the RBP has been designed. It consists of a number of points divided into ”before”, “during” and “after” the consultation. Interviews with selected Sami groups in Västerbotten have been the base to this evaluation of the model's effectiveness. The communication model is a well designed tool, but has not been actively used that much. The reason for this is that many groups isn’t sufficiently complete with their RBP to use this in consultation, as well as the communication model recently been published. Many groups use unconsciously parts of the model at the consultations. The interest in education of the use of RBP is large. We think that the communication model is important tool. It will probably not be used that much in the already effective consultations, but may be a good tool for education in the use of RBP, as well as a means in consultations where the communication is a problem. Renbruksplanen är ett kommunikations- och planeringsverktyg framtaget för samebyarna. Ett av huvudsyftena med denna är att den ska fungera som ett hjälpmedel vid samråd med andra markaktörer, däribland skogsbruket. Samebyarna har efterfrågat en modell i hur denna kan användas på ett smidigt sätt. Med Skogsstyrelsen som projektledare har en kommunikationsmodell för renbruksplanen utformats. Den består av ett antal punkter indelat i ”före”, ”under” och ”efter” samråd. Intervjuer med utvalda samebyar i Västerbotten har varit grund till denna utvärdering av modellens måluppfyllelse. Kommunikationsmodellen är ett välutformat verktyg, men har ännu inte använts aktivt i så stor utsträckning. Anledningen till detta är att många byar inte i ...